The Feldstein-Horioka puzzle or paradox after 44 Years: A fallacy of composition - Charles Yuji Horioka (Osaka University, Institute of Social and Economic Research (ISER), 2024)
The finding of Feldstein and Horioka (1980) that domestic saving and domestic investment are highly correlated across countries despite the rapid globalization and liberalization of financial markets in recent decades has been regarded as a Puzzle or Paradox. However, in this paper, we show that countries as a whole may not be able to transfer their capital abroad and that the Feldstein-Horioka Finding of domestic saving and domestic investment being highly correlated across countries may arise even if there are no frictions in financial markets and even if individual investors can freely transfer their capital abroad if there are frictions in goods markets such as transport costs, tariffs, nontariff barriers, the cost of regulatory compliance, etc. In fact, there is evidence that frictions in goods markets are a more serious impediment to countries as a whole being able to transfer their capital abroad than frictions in financial markets, especially in the short run.
Keywords: F15; F21; F32; F36; F41; G15; 330; Capital controls; fallacy of composition; Feldstein-Horioka Finding; Feldstein-Horioka Puzzle or Paradox; frictions in financial markets; frictions in goods markets; global interest rate; globalization and liberalization of financial markets; interest parity; interest rate equalization; international capital flows; international capital mobility; saving-investment correlations; saving retention coefficient; trade costs; trade frictions